Fractional technologies of a food GRAIN CLEANING - U.I. ERMOlJEV; M.U. Kochkin (Advanced Engineering Research)
An experimental research of fractional technologies of a food grain cleaning is executed and theirs principal results are given. Key words: fractional technology, experimental research, food grain, cleaning, experimental cleaning grain unit.